2021
DOI: 10.1108/ijph-11-2020-0089
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the COVID-19 lockdown on drug service provision in European prisons

Abstract: Purpose This paper aims to describe the impact of the COVID-19 containment measures on the provision of drug treatment and harm reduction services in European prisons in15 countries during the early phase of the pandemic (March –June 2020). Design/methodology/approach The paper is based on a mixed method research approach that triangulates different data sources, including the results of an on-line survey, the outcome of a focus group and four national case studies. Findings The emergence of COVID-19 led t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 6 publications
(5 reference statements)
1
22
0
2
Order By: Relevance
“…According to human rights organizations, the pandemic aggravated the situation of detained persons due to excessive confinement and quarantine ( Amnesty International, 2021 ; Harm Reduction International, 2023 ). On the grounds that more restrictive conditions of detention reduce the risk for transmission of SARS-CoV-2, numerous European penal authorities suspended external service providers and psychological group counseling ( Kennedy et al, 2021 ; Montanari et al, 2021 ; Puzzo, Aldridge-Waddon, Stokes, Rainbird, & Kumari, 2022 ). In line with these reports, our study highlights the substantial impact of COVID-19 on forensic care in terms of rehabilitative activities and visitations in Austria.…”
Section: Discussionmentioning
confidence: 99%
“…According to human rights organizations, the pandemic aggravated the situation of detained persons due to excessive confinement and quarantine ( Amnesty International, 2021 ; Harm Reduction International, 2023 ). On the grounds that more restrictive conditions of detention reduce the risk for transmission of SARS-CoV-2, numerous European penal authorities suspended external service providers and psychological group counseling ( Kennedy et al, 2021 ; Montanari et al, 2021 ; Puzzo, Aldridge-Waddon, Stokes, Rainbird, & Kumari, 2022 ). In line with these reports, our study highlights the substantial impact of COVID-19 on forensic care in terms of rehabilitative activities and visitations in Austria.…”
Section: Discussionmentioning
confidence: 99%
“…Several US studies reported the proportion of cases that died: 0.5% (3/568) in New York City jails from March to April 2020 [59], 1.1% (7/628) in a jail in Illinois from March to April 2020 [50], 0.6% (7/1,240) in prisons and jails in Connecticut from March to June 2020 [60], ranging from 0% to 0.9% based on surveillance data for prison systems from March to July 2020 [38], 0.5% in state prisons in California from March to October 2020 [32], 0% of 382 cases in Idaho, USA between July and November 2020 [47], and 0.7% in a Utah outbreak from September 2020 to January 2021 [55]. A European study reported 0 deaths of 26 cases (0%) in Belgium between March and June 2020, 1 death of 119 cases (0.8%) in France by mid-May 2020, and 4 deaths in 315 cases (1.3%) in Italy between March 9 th and May 4 th , 2020 [67]. In Quebec, Ontario and British Columbia, Canada, the case fatality ratio in federal prisons was higher than that of the general population between March and May 2020: 0.5% compared with 0.3% [43].…”
Section: Plos Onementioning
confidence: 99%
“…There has even been a suicide in [name of prison]." 67 Many incarcerated individuals described how isolation exacerbated depression, anxiety, thoughts of self-harm, and suicidal ideation [78,81].…”
Section: Plos Onementioning
confidence: 99%
“…The level of coordination and joint commitment of the health and prison authorities was outstanding, while the inmates themselves played an equally important role in the measures for prevention and control of transmission and vaccination. One notable example is the major reduction in the prison population and the releases that took place to avoid transmission of SARS-CoV-2 in the early days of the pandemic and lockdown 5 .…”
mentioning
confidence: 99%